2019
DOI: 10.1111/tmi.13296
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of Option B+ ART in Malawi: few severe maternal toxicity events or infant HIV infections among pregnant women initiating tenofovir/lamivudine/efavirenz

Abstract: Objectives Malawi's Option B+ universal antiretroviral therapy (ART) program for pregnant and breastfeeding women does not include routine laboratory monitoring. We report safety outcomes of pregnant women who initiated ART through Option B+. Methods We analysed 12‐month data from an observational cohort study on Option B+ among women newly initiating tenofovir/lamivudine/efavirenz (TDF/3TC/EFV) at a government antenatal clinic in Lilongwe, Malawi. Proportions of women engaged in care, incidence of DAIDS grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…After treatment with AZT + 3TC + LPV/r, HGB and RBC counts significantly decreased in rats, which may be related to the inhibition of erythrocytes by damaging the chromosomes. Patients can also develop anaemia after treatment with AZT, 3TC or LPV/r 26,31 . The increased apoptosis associated with DNA strand breaks further confirmed the genotoxicity of AZT + 3TC + LPV/r, which also decreased the lymphocyte percentage in rats.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…After treatment with AZT + 3TC + LPV/r, HGB and RBC counts significantly decreased in rats, which may be related to the inhibition of erythrocytes by damaging the chromosomes. Patients can also develop anaemia after treatment with AZT, 3TC or LPV/r 26,31 . The increased apoptosis associated with DNA strand breaks further confirmed the genotoxicity of AZT + 3TC + LPV/r, which also decreased the lymphocyte percentage in rats.…”
Section: Discussionmentioning
confidence: 68%
“…However, some studies have reported that PMTCT drugs may adversely affect the body. Some patients who received AZT, 3TC and LPV/r alone or in combination experienced side effects such as headache, fatigue, nausea and vomiting, bone marrow suppression, leukopenia and anaemia 12,13,26 . Although for the most commonly used triple drug for AIDS PMTCT, systemic safety evaluation information for AZT + 3TC + LPV/r is scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected for this review were summarised in Table 2, which identified 22 studies from 11 African Countries that met inclusion criteria (Cameroon, Ethiopia, Lesotho, Malawi, Rwanda, South Africa, Swaziland, Tanzania, Uganda, Zambia and Zimbabwe). Study designs varied as follows: there were 13 retrospective cohort studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] ; five prospective cohort studies [37][38][39][40]45 ; two cross-sectional studies 41,42 and one randomised control trial (RCT). 43 Sample sizes ranged from 124 13,15 to 2505 women.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16 studies reported MCTC rates of >2% to 5% with Option B+ implementation. Studies were from Cameroon, 24 Ethiopia at 2 years, 25,27 Lesotho at 2 years, 44 Malawi, 28,29,30,41,42 Rwanda at 2 years, 31 Swaziland, 37 Tanzania, 42 Zambia 33,34,40 and Zimbabwe. 36 A study from Uganda 32 and a study from Zambia 34 reported MTCT rates of above 5%, surpassing the WHO target for elimination of HIV transmissions from mother to child.…”
Section: Mother-to-child Transmission Of Hiv In Option B+mentioning
confidence: 99%